Application of low-intensity ultrasound as a rapid, cost-effective tool to wheat screening: Discrimination of Canadian varieties at 10 MHz. (July 2019) - Salimi Khorshidi, Ali; Ames, Nancy; Cuthbert, Richard; Sopiwnyk, Elaine; Thandapilly, Sijo Joseph
Abstract: Our previous study on the use of low-intensity ultrasound for wheat variety discrimination showed the potential of ultrasound waves at 10 MHz for wheat screening and dough rheology evaluation. To further examine the reliability of the technique for wheat variety differentiation at 10 MHz, 23 hard red spring (HRS) wheat varieties with comparable bread making quality were studied. Wheat quality characteristics determined with farinograph, extensograph and baking test were used for comparison purposes. Highly significant effect (P ≤ 0.001) of variety on ultrasonic parameters as well as principal component analysis results confirmed the capability of the technique at 10 MHz for wheat variety discrimination. Ultrasonic parameters were also demonstrated to be significantly correlated (P ≤ 0.05) with wheat protein content, falling number and grain ash content. Subgrouping wheat varieties based on their grain and flour characteristics promoted significant correlations between ultrasound and dough strength parameters. High sensitivity of ultrasound signals to protein, starch and microscopic inhomogeneities, e.g., tiny air bubbles and particles, enabled discrimination of Canadian varieties used in this study. Accordingly, further modification of the current protocol is believed to broaden the application of our low-intensity ultrasound technique at 10 MHz to wheat screening and quality evaluation from various angles. Highlights: Ultrasound (10 MHz) was highly sensitive to differences among wheat varieties. Rheological properties of wheat flour doughs could be easily evaluated by ultrasound. Ultrasound was more sensitive to wheat minerals compared to conventional methods. A starting point to the development of a promising screening tool was established. Further applications of ultrasound at 10 MHz to cereals was foreseen.